Analisis Kemampuan dalam Menyelesaikan Masalah Literasi Matematika Ditinjau dari Emotional Intelligence (EI) Siswa Kelas X - Dassa, Awi; Arwadi, Fajar; Damayanti, Isti Qama (Issues in Mathematics Education (IMED), 2024)
This study aims to describe the ability in mathematical literacy problems solving in terms of Emotional Intelligence (EI) of class X students of Senior High School 4 Maros. This research is qualitative research with a descriptive approach. The research subjects were taken purposively, namely 1 each from category of emotional intelligence. The instruments in this study is namely EI questionnaires, mathematical literacy tests, and interview guidelines. The indicators used consist of 6 levels of ability in solving PISA mathematical literacy problems according to the OECD. The results showed that: 1) Optimal category students are able to answer questions in a general context, addition to extracting relevant information, performed procedures applied simple problem-solving strategies, and conceptualized. 2) Special category students are able to answer questions in a general context, extract relevant information, carry out procedures sequentially, apply simple problem-solving strategies and conceptualize. 3) Vulnerable category students are able to answer questions in a general context, extract relevant information, carry out procedures sequentially, implement simple problem-solving strategies, and work effectively by involving assumptions. 4) Need alert category students are able to answer questions in a general context